How accurately do routinely reported HIV viral load suppression proportions reflect progress towards the 90-90-90 target in the population on ART in Khayelitsha, South Africa? - Euvrard, Jonathan George (Department of Public Health and Family Medicine, 2019)
Background: In 2016, Khayelitsha reported almost 89% viral load (VL) suppression but less than 56% completion on routine quarterly reports, casting doubt on the validity of reported suppression. Objectives: To assess the validity of reported VL suppression as a measure of progress towards the 90-90-90 target and identify barriers to routine VL completion. Methods: A retrospective cohort study including all patients on antiretroviral treatment (ART) in Khayelitsha with a routine VL expected between 1 July 2015 and 30 June 2016 was conducted. ART programme and laboratory data were obtained and a sample of 1 035 patient folders were reviewed. Suppression was calculated using laboratory data and compared to reported suppression. A VL cascade from “expected” to “done”, “filed”, “noted” and “captured” was constructed to reflect the steps a VL must complete to be included in reported suppression and successful progression to each step was estimated. Logistic regression models were used to calculate adjusted odds ratios (aOR) with 95% confidence intervals (95%CI) for completion among different patient groups. Results: Using laboratory data, VL suppression was estimated to be 82%, 87%, 89% and 91% at the 50, 200, 400 and 1 000 copies/mL thresholds respectively, but reported suppression would have been 80%, 86%, 88% and 89% at those thresholds. Of 22 991 patients with a routine VL due in the study period, 84% were done, 79% filed, 76% noted, and 55% captured. Routine VL were more likely to be done among children< 15 years old (aOR 1.89, 95%CI 1.45–2.48) and pregnant women (aOR 1.90, 95%CI 1.28–2.81) compared to adult men, adjusted for facility. Conclusion: Despite low reported completion, actual completion was high and reported suppression was similar to suppression calculated using laboratory data, thus providing an accurate measure of progress towards the 90-90-90 target. More work is needed to reach the 16% of patients missed by routine testing. Most of the VL done were available to the clinician at the next assessment, and further research is needed to assess how effectively these VL results are used in clinical decision-making.